Clinical value of RAG1 expression and IKZF1 deletions in Philadelphia negative pediatric B cell precursor acute lymphoblastic leukemia. (3rd July 2020) - Aref, Salah; Khaled, Nada; Menshawy, Nadia El; Sabry, Mohamed; Agder, Mohamed Al
Abstract: This study aimed to address the clinical impact of recombination-activating gene (RAG1) expression and tumor suppressor IKZF1 gene deletions in Philadelphia negative B-cell precursor acute lymphoblastic leukemia (B-ALL) patients. Fifty newly diagnosed pediatric Philadelphia negative B-ALL patients were included in this study. Using Bone Marrow samples, RAG1 expression was assessed by real time PCR and IKZF1 deletions were determined by multiplex real-time quantitative PCR. The expression of RAG1 was significantly higher in B-ALL patients as compared to the controls ( p < .001). The B-ALL patients with RAG1 high expression (≥median) had lower response to induction of remission, shorter DFS, shorter overall survival, higher blast cells, and white cell counts in the peripheral blood as compared to those with low RAG1 expression levels ( p < .01 for all). Likewise, there was significant association between IKZF1 deletion and high RAG1 expression. Based on our findings RAG1 high expression and IKZF1 deletions were associated with adverse prognosis in Philadelphia negative B-ALL. RAG1 could be used as therapeutic target in the treatment of B-ALL.